2021
DOI: 10.7150/thno.65064
|View full text |Cite
|
Sign up to set email alerts
|

Multiple regression analysis of a comprehensive transcriptomic data assembly elucidates mechanically- and biochemically-driven responses to focused ultrasound blood-brain barrier disruption

Abstract: Background: Focused ultrasound (FUS) blood brain barrier disruption (BBBD) permits the noninvasive, targeted, and repeatable delivery of drugs to the brain. FUS BBBD also elicits secondary responses capable of augmenting immunotherapies, clearing amyloid-β and hyperphosphorylated tau, and driving neurogenesis. Leveraging these secondary effects will benefit from an understanding of how they correlate to the magnitude of FUS BBBD and are differentially affected by the mechanical and biochemical stimu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 61 publications
0
12
0
Order By: Relevance
“…Previous studies have revealed that BBB opening by ultrasound is a reversible process and that it is fully restored after 24 h as measured by contrast‐enhanced MRI. 23 Our previous studies have observed a reduction in Aβ plaque load following an ultrasound treatment paradigm consisting of five to seven treatments repeated on a weekly basis, 13 whereas other studies have observed a response in bulk tissue (including microglia) ranging from 1 week after 6 weekly treatments, 26 and 6 27 , 28 and 24 h 27 , 29 , 30 after a single treatment. As microglia are a cell population presenting with a fast and dynamic response depending on both the intensity and time‐point after stimulation (acute vs. chronic response), we sought to observe the transcriptomic changes in these cells outside of the acute response of microglia to BBB opening.…”
Section: Discussionmentioning
confidence: 97%
“…Previous studies have revealed that BBB opening by ultrasound is a reversible process and that it is fully restored after 24 h as measured by contrast‐enhanced MRI. 23 Our previous studies have observed a reduction in Aβ plaque load following an ultrasound treatment paradigm consisting of five to seven treatments repeated on a weekly basis, 13 whereas other studies have observed a response in bulk tissue (including microglia) ranging from 1 week after 6 weekly treatments, 26 and 6 27 , 28 and 24 h 27 , 29 , 30 after a single treatment. As microglia are a cell population presenting with a fast and dynamic response depending on both the intensity and time‐point after stimulation (acute vs. chronic response), we sought to observe the transcriptomic changes in these cells outside of the acute response of microglia to BBB opening.…”
Section: Discussionmentioning
confidence: 97%
“…Albumin entry into the parenchyma of brain induces neuroinflammation triggered by the NFκB pathway [201]. This SIR response, which is similar to that observed in cerebral ischemia or traumatic brain injury [201], is associated with the up-regulation of >1000 genes within 6-24 h of the FUS-MB treatment [235]. A recent review [236] suggests that optimization of ultrasound parameters may allow for "safe" BBBD.…”
Section: Bbbd Following Intravenous Microbubble/focused Ultrasoundmentioning
confidence: 89%
“…If this is true, then would not BBBD have serious toxicity in the brain? Indeed, the most developed forms of BBBD, ICAHM and FUS-MB, both cause a non-infectious inflammation in brain called a sterile inflammatory response (SIR) [200,201,235]. ICAHM was demonstrated over 30 years ago to cause vascular pathology in brain [202], and chronic neuropathologic effects in brain [203].…”
Section: Miscellaneous Forms Of Bbbdmentioning
confidence: 99%
“…Despite these encouraging findings and extended work on healthy brains and brain tumors, as well as other disease models (e.g., Alzheimer's) (25,(29)(30)(31)(32), the treatment window (i.e., FUS exposure) to elicit distinct immuno-mechano-biological effects and promote effective therapeutic trafficking in the brain TME remains poorly defined. This is because current studies in brain tumors typically report only the estimated focal pressure (26)(27)(28)32) and not the MB acoustic emissions generated during the sonication (29,33,34), which is critical for making accurate inferences about the strength and type (stable versus inertial) of the MB oscillation. Moreover, current investigations offer limited insights on the penetration and uptake of immune adjuvants, such as anti-PD1, in the brain TME (27,28), which hinders our ability to fully assess the presumed advantages of the proposed strategy.…”
Section: Introductionmentioning
confidence: 99%